Development and evaluation of low-pH concrete plugs suitable for high-level radioactive waste repositories - Seokgu Gang; Daewon Lee; Jin-Seop Kim; Youngjin Shin; Jongwon Jung (Case Studies in Construction Materials)
In this study, low-pH concrete mixtures suitable for use as plugs in high-level radioactive waste disposal sites were evaluated by designing thirteen mixtures with various ratios of binders, including silica fume, fly ash, and blast furnace slag, and fillers, such as limestone and quartz. Three mixture designs that satisfied both the compressive strength requirement (>50 MPa) and leachate pH criterion (<11) after 28 d of curing were selected for further investigation. Their compressive and split tensile strengths, chloride-ion diffusion coefficient, and leachate pH were experimentally evaluated. The use of fly ash and silica fume as binders resulted in higher early compressive strengths. No mixture design exhibited significant long-term strength degradation after curing at 40 °C. The split tensile strength values were lower than those reported in previous studies, which is attributed to the suboptimal pore size distribution of the fine aggregates used in this study. The use of both limestone and quartz (SiO2) as fillers resulted in the lowest chloride-ion diffusion coefficient, with all mixture designs exhibiting excellent resistance to chloride-ion diffusion. The leachate pH remained < 11 throughout 63 d of curing. Additionally, the compressive strength increased with an increasing leachate pH. The leachate pH was influenced by the surface area characteristics of silica fume, contrary to that previously reported. An increasing pH resulted in a higher silica content in the leachate solution, affecting the swelling characteristics of the bentonite used as backfill.